A prospective study of relationship of vascular pedicle width and central venous pressure with ventilator parameters in ventilated patients - Mohd Fahmi, Lukman (2008)
The objective of this study is to determine relationship ofVascular Pedicle Width (VPW), Central Venous Pressure (CVP), Positive End Expiratory Pressure (PEEP) and Peak Inspiratory Pressure (PIP) in adult ventilated patients using single supine chest radiograph. This was prospective, randomized study and had been approved by the Research and Ethics Committee, School Of Medical Sciences, Universiti Sains Malaysia. One-hundred and forty adult ventilated patients in Intensive Care Unit (ICU) and Neuroscience Intensive Care Unit of Hospital Universiti Sains Malaysia (HUSM) involved, from May 2006 until December 2006. CVP, PEEP and PIP was taken within 1 hour after chest radiograph taken. VPW was measured on digitalized chest radiograph by Radiology Researcher at separate occasion without clinical data related to patient's condition. There was a significant linear relationship between CVP and VPW (p<0.001, CI 0.48- 0.97 mmHg), with those who had CVP of 10 mmHg will have VPW wider for 7 .3mm. There was also significant linear relationship between PEEP and VPW {p<0.05, CI 0.00-0.97 cmH20) with those who had PEEP of 10 em H20 have VPW wider for 4.9mm. However, there was no significant linear relationship between PIP and VPW. There was no interaction between independent variables. From these three variables, CVP has a strongest correlation with VPW, which indicate it's usefulness in ICU. PEEP and PIP, served as ventilator parameters, have weaker relationship with VPW which makes implementation of VPW in ventilated patient regardless of ventilator setting become valuable.